A bifunctional fluorinated ether co-solvent for dendrite-free and long-term lithium metal batteries. (May 2022) - Zhang, Guangzhao; Deng, Xiaolan; Li, Jiawei; Wang, Jun; Shi, Guoli; Yang, Yu; Chang, Jian; Yu, Kai; Chi, Shang-Sen; Wang, Hui; Wang, Peng; Liu, Zhongbo; et al.
Abstract: The employment of localized high concentration electrolytes (LHCEs) has been demonstrated as an effective strategy for the fabrication of next-generation high-energy-density lithium metal batteries. However, the low ionic conductivity of LHCEs and their parasitic side reactions with lithium metal anodes severely hinder the cycling stability of lithium metal batteries. Herein, a partially fluorinated ether of bis (2, 2-difluoroethyl) ether (BDE) is proposed as a bifunctional co-solvent to form novel LHCEs for realizing dendrite-free and long-term lithium metal batteries. The BDE co-solvent serves as a diluent to improve the ionic conductivity up to 6.4 mS/cm by dissociating lithium salt via weak interaction and decreasing the electrolyte viscosity. In addition, the BDE co-solvent could promote the formation of uniform lithium fluoride (LiF)-rich solid electrolyte interphase (SEI) to suppress the dendrite deposition by regulating the solvation shell structure, resulting in high Coulombic efficiency of 99.6%. As a result, the assembled full cell exhibits outstanding cycling stability (97% capacity retention after 200 cycles @0.5 C) with high areal capacity (2 mAh/cm 2 ) and high rate capability (2 C) under practical conditions (50 µm Li, lean electrolyte: 3 g/Ah). We also demonstrate the real application of electrolyte with a commercial cathode in 320-mAh-level pouch cells. Graphical Abstract: ga1 Highlights: A partially fluorinated ether was prepared as a bifunctional electrolyte co-solvent. Dendrite-free and long-term lithium metal batteries were developed. Li plating/stripping Coulombic efficiency was high up to 99.6%. Outstanding cycling stability of a 320-mAh-level pouch cell was achieved.